Drag evaluations on rough surfaces from near-wall models - Friedmann, Elfriede; Kim, Y.; Ri, Y. (Conference "Topical Problems of Fluid Mechanics 2017", 2017)
In this paper we evaluate the drag of periodic rough microstructures from near-wall models. With near-wall models we denote Coutte ows which describe the viscous boundary layer of turbulent ows. The structures inside this layer are not the optimal ones but can be used for a deeper understanding of the drag reducing mechanism of riblets due to a valid mathematical theory for viscous ows. Here, the numerical calculations can be validated and the developer calculation strategies can later be extended to the turbulent boundary layer. The focus of this paper is the evaluation of the drag of several microstructures for a better understanding of their action to the turbulent overow
Die vollständigen Namen des zweiten und dritten Autors sind nicht ermittelbar
Gesehen am 17.09.2018